Alignment of the Recreation Business Management Curriculum with Tourism Industry Competency Requirements - Urai Muhani; Urai B Asnol; Ismail Umar; Abd Halim (AL-ISHLAH: Jurnal Pendidikan, 2026)
The rapid transformation of the tourism industry toward digitalization, sustainability, and experience-based services requires higher education curricula to align with evolving competency demands. However, limited studies have systematically examined the alignment between the Semester Learning Plan (Rencana Pembelajaran Semester—RPS) and industry-required competencies in tourism education.This study employed a qualitative-descriptive approach integrating a Systematic Literature Review (SLR), curriculum document analysis, semi-structured interviews with academic staff, and surveys of industry practitioners and alumni. The SLR covered publications from 2018 to 2024 to identify key competency trends, while empirical data were used to assess curriculum implementation and relevance.The findings indicate that the RPS sufficiently addresses foundational competencies such as business management, customer service, and tourism operations. However, significant gaps were identified in digital marketing, data-driven decision-making, tourism technology utilization, and sustainability practices. Industry stakeholders highlighted the need for greater emphasis on practical skills, technological readiness, and experiential learning.These findings suggest that current curricula remain predominantly theoretical and insufficiently responsive to industry transformation. This study proposes a more adaptive, industry-driven curriculum model that integrates digital and sustainability competencies while strengthening academic–industry collaboration. The study contributes to the literature by offering a comprehensive curriculum–industry alignment framework informed by multi-source data, with implications for improving graduate employability and curriculum relevance in tourism education.